2011
DOI: 10.1104/pp.111.180414
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Biochemical Characterization of a Novel Ecto-Apyrase, MP67, from Mimosa pudica        

Abstract: We have previously reported the presence of an apyrase in Mimosa pudica. However, only limited information is available for this enzyme. Thus, in this study, the apyrase was purified to homogeneity. The purified enzyme had a molecular mass of around 67 kD and was able to hydrolyze both nucleotide triphosphate and nucleotide diphosphate as substrates. The ratio of ATP to ADP hydrolysis velocity of the purified protein was 0.01 in the presence of calcium ion, showing extremely high substrate specificity toward A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…10 The specific activity of MP67 for the hydrolysis of ADP is extremely higher than for the hydrolysis of ATP. 7 The biochemical uniqueness of MP67 can be further demonstrated by differences in sensitivity to inhibitors. Apyrases are generally known to be insensitive to inhibitors of P-type, F-type and V-type ATPases; however, MP67 is sensitive to inhibitors of P-type ATPases.…”
Section: Apyrasementioning
confidence: 99%
See 4 more Smart Citations
“…10 The specific activity of MP67 for the hydrolysis of ADP is extremely higher than for the hydrolysis of ATP. 7 The biochemical uniqueness of MP67 can be further demonstrated by differences in sensitivity to inhibitors. Apyrases are generally known to be insensitive to inhibitors of P-type, F-type and V-type ATPases; however, MP67 is sensitive to inhibitors of P-type ATPases.…”
Section: Apyrasementioning
confidence: 99%
“…Apyrases are generally known to be insensitive to inhibitors of P-type, F-type and V-type ATPases; however, MP67 is sensitive to inhibitors of P-type ATPases. 7,10,11 Moreover, although the MP67 enzyme contains the typical apyrase conserved region ACR1-5, comparison of the primary sequences showed that MP67 and MpAPY2 share only 45% identity. Phylogenetic analyses showed that MP67 is a noncanonical apyrases.…”
Section: Apyrasementioning
confidence: 99%
See 3 more Smart Citations